BEHAVIOUR OF CHEMICAL SPECIES UNDER REDUCING CONDITION IN A SUBAQUEOUS SOILS COLUMN - Y. Hiroshiro; K. Jinno; T. Yokoyama; S. I Wada (International Association of Lowland Technology, 1999)
In order to model the transport of multicomponent species including Mn2+ and Fe2+ from reduced layer to oxidized layer similar to paddy field condition, a preliminary column experiment was carried out. To reproduce actual paddy field conditions, the upper part of the column was filled with the soil taken from the paddy field and fine granite soil was filled in the lower soil of column. The experimental result showed that ORP (Oxidation Reduction Potential) rapidly decreased for first two days after the beginning of this experiment, and then showed a constant value, NO3 concentration in plow layer rapidly decreased due to the denitrification. On the other hand, the concentartions of dissolved Mn2+ and Fe2+ gradually increased after OPR achieved to a steady value, and they kept constant concentrations for 30 days.